HAEMATOLOGICAL, BIOCHEMICAL, AND HISTOPHATOLOGY OF Clarias gariepinus FINGERLINGS FED VARYING LEVELS OF PROCESSED (B90MIN/S72HRS) Moringa oleifera SEED MEAL - HARUNA, M. A; IPINJOLU, J.K.; UMAR, M. (Nigerian Journal of Fisheries, 2025)
This study evaluated the health status of Clarias gariepinus fingerlings fed graded levels of Moringa oleifera seed meal. Five isonitrogenous and isocaloric diets were formulated, in which the treated (B90min/S72hrs), seed meal, replaced fish meal at 0, 20, 40, 60 and 80 %, and fed to the fingerlings for twelve weeks. The highest weight gain (12.77±1.14g) was observed in the fish fed the control diet but was not significantly different from dietary treatment T2 in which fish meal was substituted with Moringa seed meal at 20 %. Mean length increase 10.17±0.45, 10.13±0.55, and 10.07±0.42cm was statistically similar in the fish fed diets with 0, 20, and 40% replacements of fishmeal respectively. Fish haematology, biochemical, liver, and kidney histopathology were determined. Red blood cells increased while protein, cholesterol, and albumin decreased with increased seed meal levels. Histopathological analysis revealed normal hepatocytes of the liver and the kidneys presented normal glomerulus tissue and collecting ducts for all the treatments. The findings on the haematological, biochemical and histopathology of the fingerlings suggest that Moringa seed meal can replace fish meal up to 40 % substitution level with no deleterious effect on the health status of the fish